Self-management of depression and anxiety amongst frail older adults in the United Kingdom: A qualitative study. - Pushpa Nair; Kate Walters; Su Aw; Rebecca Gould; Kalpa Kharicha; Marta College Buszewicz; Rachael Frost (PLoS ONE, 2022)
Objectives Depression and anxiety are common in frail older people and are associated with high levels of morbidity and mortality, yet they typically face greater barriers to accessing mental health treatments than younger people and express preferences for self-managing their symptoms. This study aims to explore frail older adults' experiences of self-managing symptoms of depression and/or anxiety. Design Qualitative semi-structured interviews, exploring experiences of depression and/or anxiety, ways participants self-managed these and the contexts within which this took place. Interviews were audio-recorded and transcribed verbatim. Participants 28 frail older adults in the United Kingdom, purposively sampled for neighbourhood, frailty and symptoms of anxiety/depression. Analysis Thematic analysis to inductively derive themes from the data. Results Our findings suggest that frail older adults find maintaining independence, engaging in meaningful activities, and socialising and peer support important for self-managing depression and anxiety. These could all be adapted to the level of frailty experienced. Drawing on life experiences, addressing the perceived cause and faith were helpful in some situations and for some personalities. Distraction and avoidance were helpful for more severe symptoms or where the causes of symptoms could not be resolved. Self-management strategies were less well-established for anxiety symptoms, especially when linked to newer health fears and worries about the future. Conclusions Developing services and sources of information that support and facilitate key therapeutic components of self-management, which align with older adults' preferred coping styles and take into account levels of frailty, may be a way of supporting frail older people waiting for mental health treatments or those who prefer not to access these. Greater awareness of anxiety and how it can be self-managed in frail older people is needed.